An exploration of the ‘African (Union Commission’s) perspective’ of quality and quality assurance in higher education: Latent voices in the African Quality Rating Mechanism (AQRM) - Nabaho, Lazarus; Turyasingura, Wilberforce (Latent voices in the African Quality Rating Mechanism, 2019)
Quality assurance of African higher education is at the top of the region’s development agenda. Prompted by the imperative to enhance the quality of higher education, the Africa Union Commission is implementing the African Quality Rating Mechanism (AQRM). The AQRM is a continental tool that affords higher education institutions an opportunity to conduct self-assessment and compare their performance against similar institutions based on a set of common criteria. The mechanism is envisaged to engender institutional cultures of quality and enhance the quality of African higher education. However, a dearth of knowledge exists about the latent notions of quality in higher education that the AQRM aims to assure and the implicit institutional-level quality assurance practices in the AQRM. Therefore, this interpretivist article, based on a review of the AQRM survey questionnaire, answered the following research question: What notions of quality in higher education and the institutional-level quality assurance practices are inherent in the quality standards of the AQRM survey questionnaire? The findings revealed that quality as fitness for purpose and exceptional are the notions of quality in higher education in the AQRM.
Keywords: Quality; quality assurance; perspectives; Africa; African Union.